Pengembangan E-Modul Asam Basa Berbasis Literasi Sains - Nadya Ulfa; Ani Sutiani (Edukimia, 2021)
Teaching material is one of the aspects to improve scientific literacy skills had by students, but based on the analysis of school textbooks, especially on acid-base materials, 2 chemistry textbook do not yet have the maximum application of scientific literacy. The aim of this research is to develop acid base e-module based on scientific literacy. The method implemented is Research and Development (R and D) method by Borg and Gall which is limited to 7 out of 10 stages. The instrument used in this study was questionnaire of validity and practicality. Validation was carried out by 5 validators while the practicality test was distributed to 2 chemistry teachers and 20 students of Class XI Science of SMA Negeri 10 Medan. Based on the validation results obtained from the validators, the average result is 4,70 which a very feasible criteria. The average value of teachers and students practicality responses was 4,60 and 4,42 with a very feasible criteria so it was concluded the acid-base e-module based on scientific literacy is valid, practical and also feasible to be used in learning activities for high school students. The follow-up of this research is to conduct a trial of the effectiveness of using e-modules in improving students’ scientific literacy skills.